Antileishmanial activity of diterpene acids in copaiba oil - dos Santos, Adriana Oliveira (Instituto Oswaldo Cruz, Ministério da Saúde, 2013)
Leishmaniasis is a neglected tropical disease. According to the World Health Organization, there are approximately 1.5-two million new cases of cutaneous leishmaniasis each year worldwide. Chemotherapy against leishmaniasis is based on pentavalent antimonials, which were developed more than a century ago. The goals of this study were to investigate the antileishmanial activity of diterpene acids in copaiba oil, as well as some possible targets of their action against Leishmania amazonensis. Methyl copalate and agathic, hydroxycopalic, kaurenoic, pinifolic and polyaltic acids isolated from Copaifera officinales oleoresins were utilised. Ultrastructural changes and the specific organelle targets of diterpenes were investigated with electron microscopy and flow cytometry, respectively. All compounds had some level of activity against L. amazonensis. Hydroxycopalic acid and methyl copalate demonstrated the most activity against promastigotes and had 50% inhibitory concentration (IC(50)) values of 2.5 and 6.0 µg/mL, respectively. However, pinifolic and kaurenoic acid demonstrated the most activity against axenic amastigote and had IC(50) values of 3.5 and 4.0 µg/mL, respectively. Agathic, kaurenoic and pinifolic acid caused significant increases in plasma membrane permeability and mitochondrial membrane depolarisation of the protozoan. In conclusion, copaiba oil and its diterpene acids should be explored for the development of new antileishmanial drugs.